Minat Berkarir di Bidang Perpajakan Pada Mahasiswa Akuntansi di Universitas Bengkulu dan Universitas Sriwijaya - Asyurah Ayu Kristalina; Danang Adi Putra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of education costs, tax volunteer programs, professional recognition, and digitalization on accounting students’ interest in pursuing careers in the field of taxation at the University of Bengkulu and Sriwijaya University. This research employed a quantitative approach using purposive sampling techniques. Data were collected through questionnaires distributed to 171 accounting students who had completed taxation courses. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results of the study indicate that education costs, tax volunteer programs, professional recognition, and digitalization partially and simultaneously have a positive and significant influence on students’ interest in pursuing careers in taxation. Professional recognition emerged as the most dominant variable influencing students’ career interests, as students tend to consider recognition, certifications, and opportunities for self-development when choosing a career path. In addition, tax volunteer programs provide practical experience that enhances students’ understanding of the taxation field, while digitalization creates the perception that taxation is a modern, efficient, and technology-oriented profession. Education costs also encourage students to pursue careers that are considered to offer promising long-term prospects and benefits in line with the educational investment they have made. The findings of this study suggest that increasing practical experience, strengthening professional recognition, and developing digital-based taxation systems can serve as effective strategies to enhance students’ interest in pursuing careers in taxation.